2020
DOI: 10.1039/c9ra09864j
|View full text |Cite
|
Sign up to set email alerts
|

Possible scenario of forming a catalyst layer for proton exchange membrane fuel cells

Abstract: Ionomer in the catalyst layer provides an ion transport channel which is essential for many electrochemical devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…(1) ionomer-covered carbon support surface, (2) ionomercovered Pt catalyst surface, and (3) packed free ionomer between the aggregated Pt/C particles. 29 For the catalyst layer with an additional PDMS film, the PDMS film can be deposited on both the ionomer-covered and uncovered regions of the carbon and the Pt surface, as well as between the aggregated Pt/ C particles. By comparing the volume of the PDMS film with the Nafion film, the relative thickness of the PDMS films to the thickness of Nafion film can be estimated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) ionomer-covered carbon support surface, (2) ionomercovered Pt catalyst surface, and (3) packed free ionomer between the aggregated Pt/C particles. 29 For the catalyst layer with an additional PDMS film, the PDMS film can be deposited on both the ionomer-covered and uncovered regions of the carbon and the Pt surface, as well as between the aggregated Pt/ C particles. By comparing the volume of the PDMS film with the Nafion film, the relative thickness of the PDMS films to the thickness of Nafion film can be estimated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To examine these phenomena in detail, it is necessary to consider the change in the electrode structure and characteristics due to the PDMS. In the electrode, the ionomer coverage can be divided into three parts: (1) ionomer-covered carbon support surface, (2) ionomer-covered Pt catalyst surface, and (3) packed free ionomer between the aggregated Pt/C particles . For the catalyst layer with an additional PDMS film, the PDMS film can be deposited on both the ionomer-covered and uncovered regions of the carbon and the Pt surface, as well as between the aggregated Pt/C particles.…”
Section: Resultsmentioning
confidence: 99%
“…[77][78][79][80] The degree of dispersion can reach from fully lumped ionomer too perfectly dispersed ionomer, with the optimum to be found in-between. 81 The authors will address the resulting heterogeneities in ionomer coverage in a follow-up work, accounting for additional structural parameters, such as component and void fractions, ionomer dispersion and coverage, and the porous network properties. Based on this treatment, a description of mixed wettability will be possible that aligns well with previous works that employed continuous distributions of contact angles.…”
Section: Understanding Platinum Loading Reduction and Catalyst Layer ...mentioning
confidence: 99%
“…Closer examination of this agglomerate structure and of the ionomer morphology revealed that typically the ionomer film is unevenly distributed 21 24 , i.e., its coverage and thickness can vary significantly. Additionally, large ionomer aggregates that are not part of the thin film have been observed 24 26 . These variations in ionomer morphology largely impact the percolation behavior of the ionomer network and thus the proton conductivity of the CCL, as well as the volume fraction and network properties of gas-filled pores needed for oxygen supply 27 29 .…”
Section: Introductionmentioning
confidence: 99%